MRCP Combined With CT Promotes the Differentiation of Benign and Malignant Distal Bile Duct Strictures - Wang, Guang-xian; Ge, Xiao-dong; Zhang, Dong; Chen, Hai-ling; Zhang, Qi-chuan; Wen, Li (Frontiers in Oncology, 2021)
Objective: To determine whether contrast-enhanced computed tomography (CT) can promote the identification of malignant and benign distal biliary strictures (DBSs) compared to the use of magnetic resonance cholangiopancreatography (MRCP) alone and to identify imaging findings of malignant DBSs. Materials and Methods: A total of 168 consecutive patients with confirmed DBSs were reviewed. MRCP alone and MRCP combined with CT images were blindly analyzed by two radiologists, and malignant or benign DBSs were identified based on surgical findings, endoscopy findings, or follow-up. The diagnostic accuracy of the two reviewers using MRCP alone and MRCP combined with CT were evaluated. MRCP and CT features of malignant and benign DBSs were compared using multiple logistic regression analysis to identify independent malignant risk factors. Results: The diagnostic accuracy of doctor A using MRCP alone was 70.2%, but there was an obvious improvement when MRCP was combined with CT (81.5%). For doctor B, the diagnostic accuracy using MRCP alone was 85.1%, which improved in diagnostic accuracy after CT was added (89.3%). The multiple logistic regression model revealed that stricture length [odds ratio (OR) 1.070, P=0.016], angle of the DBS (OR 1.061, P<0.001), double duct sign (OR 4.312, P=0.003) and low density in the arterial phase (OR 0.319, P=0.018) were associated with malignant DBS. A scoring model incorporating these four factors was established; at a threshold value of 1.75, and the sensitivity and specificity for the detection of malignant DBSs were 73.5 and 85.9%, respectively. Conclusions: Compared to the use of MRCP alone, MRCP combined with contrast-enhanced CT can improve the accuracy of DBS diagnosis. The scoring model accurately predicts malignant DBSs and helps make treatment decisions.